PENDAMPINGAN PENINGKATAN KOMPETENSI PENGOLAHAN TEKSTIL DENGAN TEKNIK MAKRAME PADA IBU PKK DUSUN SIDODADI DESA CANGGU KECAMATAN BADAS KABUPATEN KEDIRI - Ulul Azmi; Muhammad Irsa Faisal Ulya; Ika Mila Marcelya; Toyibatussalamah Toyibatussalamah; Emma Rahmawati (LP2M Universitas Ibrahimy, 2024)
The article highlights the significance of macrame technique training as a skill that offers additional economic opportunities for PKK mothers, aiming to equip them with basic knowledge and skills in macrame techniques. It emphasizes the potential benefits of mastering macrame techniques, such as generating unique and economically valuable products, increasing productivity, and improving well-being.This article focuses on the implementation of macrame technique training to enhance the productivity of PKK (Pemberdayaan Kesejahteraan Keluarga) mothers in Sidodadi Hamlet, Canggu Village, Badas District, Kediri Regency. The community service method used in this research is ABCD (Community Asset Based Development). By applying the five steps of the ABCD approach, namely Discovery, Dream, Design, Destiny, Reflection and Evaluation. By mastering macrame techniques, PKK mothers can generate unique and economically valuable products, leading to increased productivity, additional income opportunities, and improved well-being. In conclusion, the article emphasizes that macrame technique training has brought significant benefits to the local PKK mothers. Through a series of activities involving potential identification, setting of expected goals, activity planning, and structured workflow, the training participants have successfully developed new skills in creating macrame handicrafts. The training outcomes also had a positive impact on increasing community participation, strengthening inter-resident relationships, and raising awareness of environmental sustainability.